The Longitudinal Effect of Bilingual Immersion Schooling on Cognitive Control and Intelligence*. (September 2016) - Woumans, Evy; Surmont, Jill; Struys, Esli; Duyck, Wouter
Abstract : Throughout the past century, the effects of bilingualism on general cognition have been extensively explored. Studies evolved from a negative to a more positive perspective, but longitudinal assessments of effects of bilingualism are scarce. This study investigated the long‐term effect of becoming a bilingual on the development of general intelligence and cognitive control. We followed 27 five‐year‐old children initiating bilingual kindergarten and 27 age‐matched controls enrolled in monolingual kindergarten. The two groups were similar with regard to socioeconomic status. At baseline, both groups spoke only French and performed equally on measures of intelligence, cognitive control, and verbal fluency. One year later, all children were tested again. Results revealed that, after 1 year, both groups improved similarly on verbal fluency and cognitive control. However, only children attending bilingual kindergarten improved significantly on intelligence, indicating that cognitive practice gained from acquiring a second language may improve general cognitive abilities assessed by intelligence tests, outside the verbal domain.